Synchrotron radiation-based quasi-elastic scattering using time-domain interferometry with multi-line gamma rays - Saito, Makina (Sci Rep, 2017)
We developed a multi-line time-domain interferometry (TDI) system using 14.4 keV Mössbauer gamma rays with natural energy widths of 4.66 neV from (57)Fe nuclei excited using synchrotron radiation. Electron density fluctuations can be detected at unique lengths ranging from 0.1 nm to a few nm on time scales from several nanoseconds to the sub-microsecond order by quasi-elastic gamma-ray scattering (QGS) experiments using multi-line TDI. In this report, we generalize the established expression for a time spectrum measured using an identical single-line gamma-ray emitter pair to the case of a nonidentical pair of multi-line gamma-ray emitters by considering the finite energy width of the incident synchrotron radiation. The expression obtained illustrates the unique characteristics of multi-line TDI systems, where the finite incident energy width and use of a nonidentical emitter pair produces further information on faster sub-picosecond-scale dynamics in addition to the nanosecond dynamics; this was demonstrated experimentally. A normalized intermediate scattering function was extracted from the spectrum and its relaxation form was determined for a relaxation time of the order of 1 μs, even for relatively large momentum transfer of ~31 nm(−1). The multi-line TDI method produces a microscopic relaxation picture more rapidly and accurately than conventional single-line TDI.